The Heme Transport Capacity of LHR1 Determines the Extent of Virulence in Leishmania amazonensis. - Rebecca L Renberg; Xiaojing Yuan; Tamika K Samuel; Danilo C Miguel; Iqbal Hamza; Norma W Andrews; Andrew R Flannery (PLOS Neglected Tropical Diseases, 2015)
Leishmania spp. are trypanosomatid parasites that replicate intracellularly in macrophages, causing serious human morbidity and mortality throughout the world. Trypanosomatid protozoa cannot synthesize heme, so must acquire this essential cofactor from their environment. Earlier studies identified LHR1 as a Leishmania amazonensis transmembrane protein that mediates heme uptake. Null mutants of LHR1 are not viable and single knockout strains have reduced virulence, but very little is known about the properties of LHR1 directly associated with heme transport. Here, we use functional assays in Saccharomyces cerevisiae to show that specific tyrosine residues within the first three predicted transmembrane domains of LHR1 are required for efficient heme uptake. These tyrosines are unique to LHR1, consistent with the low similarity between LHR1 and its corresponding homologs in C. elegans and human. Substitution of these tyrosines in LHR1 resulted in varying degrees of heme transport inhibition, phenotypes that closely mirrored the impaired ability of L. amazonensis to replicate as intracellular amastigotes in macrophages and generate cutaneous lesions in mice. Taken together, our results imply that the mechanism for heme transport by LHR1 is distinctive and may have adapted to secure heme, a limiting cofactor, inside the host. Since LHR1 is significantly divergent from the human heme transporter HRG1, our findings lay the groundwork for selective targeting of LHR1 by small molecule antagonists.